A Comparison of Feminist Term Translation Practices in Academic Journals of Gender and Women’s Studies in Turkiye - Göksenin Abdal; Tuba Ayık Akça (İstanbul Üniversitesi Çeviribilim Dergisi)
Feminist term translation brings both linguistic and pragmatic sides of translation together and turns the act of translation into a function-driven process rather than a solely form-based transfer. Translators, who join it under different roles such as academics, activists, or field experts, sometimes all at the same time, try to make up for the information loads and contextual definitions regarding the source terms in the target language and culture system with various translation strategies during the process of translation. This study aims to reveal practical tendencies in the feminist term translation activities in academic journals of gender and women’s studies in Turkey. In this respect, feminist term translation practices in selected texts from three journals, namely Feminist Approaches in Culture and Politics [Kültür ve Siyasette Feminist Yaklaşımlar], Kaos Q+, and Feminist Imagination: Journal of Academic Studies [Feminist Tahayyül: Akademik Araştırmalar Dergisi], which have published the most recent translations in the field, will be discussed from a comparative perspective, starting from Istanbul University Journal of Women’s Studies [Istanbul Üniversitesi Kadın Araştırmaları Dergisi], the first academic journal of gender and women’s studies in Turkey. In the analysis, the main focus is on feminist term translation strategies, while an evaluative framework will be drawn on the connections between journals’ areas of focus and feminist term translation practices applied under them.